2014
DOI: 10.1155/2014/623269
|View full text |Cite
|
Sign up to set email alerts
|

Can Preterm Labour Be Predicted in Low Risk Pregnancies? Role of Clinical, Sonographic, and Biochemical Markers

Abstract: Background and Objectives. This is a prospective nested cohort study conducted over a period of 3 years. 2644 women were recruited, out of which final analysis was done for 1884 women. Methods. Cervicovaginal and blood samples were collected for all recruited women. Out of these, 137 women who delivered before 35 weeks were treated as cases and equal number of matched controls were chosen. Analysis of samples for serum G-CSF, AFP, ferritin, and cervicovaginal interleukin-6 and IGFBP-1 was done. Results. Poor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Our results are concurrent with Singh B, et al [16], Tripathi R, et al [17], Meyer RE, et al [18], Moawad AH, et al [19], Huras H, et al [20] and Goldenberg RL, et al [21], Singh B, et al [16] reported an increase in serum ALP during PTD.…”
Section: Discussionsupporting
confidence: 87%
“…Our results are concurrent with Singh B, et al [16], Tripathi R, et al [17], Meyer RE, et al [18], Moawad AH, et al [19], Huras H, et al [20] and Goldenberg RL, et al [21], Singh B, et al [16] reported an increase in serum ALP during PTD.…”
Section: Discussionsupporting
confidence: 87%
“…17 Despite decades of research, we are no closer to finding answers in terms of prediction and hence prevention of preterm labour. 18 Documented risk factors like multiple pregnancy, placenta praevia and precious pregnancy/bad obstetric history are usually associated with indicated preterm births and hence, these were excluded from the present study as the study primarily aimed to identify non-traditional risk factors for spontaneous preterm births.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that moderate to severe anemia (9 to 10gm/dl) has been associated with a 2-3 fold increased risk of preterm labor. 9 In another work performed in Germany by Goepel et al, it was seen that preterm labor was recorded in 48% pregnant women with serum ferritin levels below 10 micrograms/liter. In our study about 58% patients had serum ferritin below 10 micrograms/liter.…”
Section: Discussionmentioning
confidence: 93%